Magnetic resonance-guided regional gene delivery strategy using a tumor stroma-permeable nanocarrier for pancreatic cancer - Wang Q (Dove Medical Press, 2015)
Qingbing Wang,1,2 Jianfeng Li,3 Sai An,3 Yi Chen,1 Chen Jiang,3 Xiaolin Wang1,2 1Department of Interventional Radiology, Zhongshan Hospital, Fudan University, 2Shanghai Institute of Medical Imaging, 3Key Laboratory of Smart Drug Delivery, Ministry of Education, Department of Pharmaceutics, School of Pharmacy, Fudan University, Shanghai, People’s Republic of China Background: Gene therapy is a very promising technology for treatment of pancreatic ductal adenocarcinoma (PDAC). However, its application has been limited by the abundant stromal response in the tumor microenvironment. The aim of this study was to prepare a dendrimer-based gene-free loading vector with high permeability in the tumor stroma and explore an imaging-guided local gene delivery strategy for PDAC to promote the efficiency of targeted gene delivery.Methods: The experimental protocol was approved by the animal ethics committee of Zhongshan Hospital, Fudan University. Third-generation dendrigraft poly-L-lysines was selected as the nanocarrier scaffold, which was modified by cell-penetrating peptides and gadolinium (Gd) chelates. DNA plasmids were loaded with these nanocarriers via electrostatic interaction. The cellular uptake and loaded gene expression were examined in MIA PaCa-2 cell lines in vitro. Permeability of the nanoparticles in the tumor stroma and transfected gene distribution in vivo were studied using a magnetic resonance imaging-guided delivery strategy in an orthotopic nude mouse model of PDAC.Results: The nanocarriers were synthesized with a dendrigraft poly-L-lysine to polyethylene glycol to DTPA ratio of 1:3.4:8.3 and a mean diameter of 110.9±7.7 nm. The luciferases were strictly expressed in the tumor, and the luminescence intensity in mice treated by Gd-DPT/plasmid luciferase (1.04×104±9.75×102 p/s/cm2/sr) was significantly (P<0.05) higher than in those treated with Gd-DTPA (9.56×102±6.15×10 p/s/cm2/sr) and Gd-DP (5.75×103± 7.45×102 p/s/cm2/sr). Permeability of the nanoparticles modified by cell-penetrating peptides was superior to that of the unmodified counterpart, demonstrating the improved capability of nanoparticles for diffusion in tumor stroma on magnetic resonance imaging.Conclusion: This study demonstrated that an image-guided gene delivery system with a stroma-permeable gene vector could be a potential clinically translatable gene therapy strategy for PDAC. Keywords: molecular imaging, magnetic resonance imaging, interventional, pancreatic cancer, genetic therapy, cell-penetrating peptides